2020
DOI: 10.1177/2036361320979216
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma: A population-based cancer registry descriptive study of 45 consecutive cases diagnosed between 1979 and 2016

Abstract: Angiosarcoma (AS) is a rare aggressive sarcoma with differentiation toward blood or lymphatic endothelium. There are few epidemiological data available on AS. To address this limitation, we investigated the epidemiological and clinical features of angiosarcoma diagnosed in a French administrative area (the Doubs department) from 1979 to 2016. A retrospective cohort study was conducted using the Doubs cancer registry database. A total of 45 patients with invasive AS were diagnosed between 1979 and 2016 in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A French registry study estimated the incidence of angiosarcoma to be 0.15 per 100 000 person-years but noted that the incidence between 2007 and 2016 was 0.26 per 100 000 person-years, higher than in the preceding decades. 8 A US-based registry study found a similar rate during that time period and also identified an increasing incidence over time specifically among older patients, most notably those older than 75 years. 9 Given the strong association of breast cancer treatment with the rare but serious later development of angiosarcoma, a previous study investigated the incidence of breast angiosarcoma in the US using the Surveillance, Epidemiology, and End Results (SEER) database across all ages and identified an increasing incidence of angiosarcoma among patients previously treated for breast cancer.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A French registry study estimated the incidence of angiosarcoma to be 0.15 per 100 000 person-years but noted that the incidence between 2007 and 2016 was 0.26 per 100 000 person-years, higher than in the preceding decades. 8 A US-based registry study found a similar rate during that time period and also identified an increasing incidence over time specifically among older patients, most notably those older than 75 years. 9 Given the strong association of breast cancer treatment with the rare but serious later development of angiosarcoma, a previous study investigated the incidence of breast angiosarcoma in the US using the Surveillance, Epidemiology, and End Results (SEER) database across all ages and identified an increasing incidence of angiosarcoma among patients previously treated for breast cancer.…”
Section: Introductionmentioning
confidence: 79%
“…Despite this progress, the true incidence of angiosarcoma remains uncertain. A French registry study estimated the incidence of angiosarcoma to be 0.15 per 100 000 person-years but noted that the incidence between 2007 and 2016 was 0.26 per 100 000 person-years, higher than in the preceding decades . A US-based registry study found a similar rate during that time period and also identified an increasing incidence over time specifically among older patients, most notably those older than 75 years …”
Section: Introductionmentioning
confidence: 99%
“…It mainly affects the proximal jejunum and the ileum. The most common clinical presentation is abdominal pain, obscure or occult gastrointestinal bleeding, anemia, and other nonspecific manifestations such as nausea, vomiting, and weight loss [ 7 ]. Acute presentation with gastrointestinal bleeding or melena is not uncommon, requiring treatment by blood transfusions (the typical presentation of our case report) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiosarcoma is a rare malignancy involving lymphatic or vascular endothelial cells that represents 1% of all soft tissue sarcomas [ 1 ]. It has an estimated incidence of about one to two cases per million [ 2 ]. These highly aggressive tumors can arise anywhere in the body, although the most common sites are cutaneous lesions of the head and neck and occasional involvement of the spleen, liver, bone, and other visceral organs.…”
Section: Introductionmentioning
confidence: 99%